Konstituierung einer Kulturlandschaft Praktiken des Kulturerbens im deutsch-tschechischen Erzgebirge - Peselmann, Arnika (Universitätsverlag Göttingen, 2018)
How does a cultural landscape come into being? And how is this process connected to the valorization of objects, sites and spaces as cultural heritage? Based on the example of the Czech-German Ore Mountains the ethnographic study investigates the relationship between practices of inheriting culture and the producton of space. With reference to anthropological heritage and policy studies, the research focuses on national and international heritage governances, particularly those of the UNESCO world heritage prorgram. How are they related to local memory discourses and practices? How do they assist in the promotion of regional tourism and other economic endeavors? What role do EU-policies on European integration play? The Czech-German Ore Mountains region is marked by post-war forced migration and resettlement. Against the background of this complex history, the study shows how collective claims on cultural property are formulated and how a shared, transboundary heritage is negotiated.